SOCIAL METABOLISM: GENERAL PRINCIPLES OF FORMATION - Крохмаль, Н. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article presents the analysis of the concept of social metabolism, traces its emergence and development in historical perspective and offers examples from different spheres of public life in which the social metabolism operates today.